(untitled) (Bangladesh Journal of Pharmacology, 2012)
The endophytic extracts of 11 fungi associated with asympomatic Artemisia annua Linn., were evaluated for antimicrobial activity against three human pathogenic microbes, Escherichia coli, Staphylococcus aureus and Trichophyton rubrum, and two plant pathogens, Rhizoctonia cerealis and Magnaporthe grisea. The results showed that these endophytic extracts had different inhibitory effects on microbial pathogens at 100 mg/mL. Among these fungal endophytes, three strains Aspergillus spp. SPS-02, SPS-04 and SPS-01 respectively showed the strongest antimicrobial activities against E. coli, S. aureu, T. rubrum. An endophytic Mucor sp. SPS-11 had the most pronounced effect on R. cerealis. Two strains Aspergillus sp. SPS-02 and Cephalosporium sp. SPS-08 exhibited the strongest antimicrobial activities against M. grisea. These anti-pathogenic endophytes could be applied as new sources of antibiotics in agriculture and pharmaceutical industry.